Penerapan Project Based Learning Pada Mata Kuliah Pancasila Dalam Memperkuat Civic Engagement Mahasiswa - Aina Nurdiyanti; Andi Aco Agus; Mirwan Fikri Muhkam; Asep Ikbal (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The commitment to Pancasila is being tested again in the midst of the development of science and technology and Society 5.0. The tendency of behavior and the rush of alternative cultures that are not in line with Pancasila must be balanced with efforts to strengthen Pancasila itself. The education sector, especially Pancasila education, is at the forefront of optimizing and preparing participatory human resources, namely graduates who are capable of maintaining national development and maintaining the resilience of the nation's ideology. The current reality shows that Pancasila education is not fully optimal in creating participatory citizens in challenging times. This research was conducted as an effort to strengthen Pancasila depreciation which is more contextual in the curricular domain through project-based learning in Pancasila courses. The type of project-based learning model that is applied is the project citizen model initiated by the Center for Civic Education (2008). This research uses a qualitative approach with a descriptive study design. The research subjects were students of Elementary School Teacher Education Study Program, Faculty of Education, State University of Gorontalo. The determination of research subjects is by purposive sampling technique. Data collection was carried out through observation, literature study, and questionnaires in the form of student response rubrics. The results of the study show that the application of Project Based Learning in Pancasila courses is able to strengthen student sociability as indicated by: (1) stimulating student sensitivity to social and national issues as well as problem solving abilities from class studies (2) students gain experience in Pancasila that is more contextual through direct field visits and carrying out impactful activities; and (3) habituation of research-based learning and research methodology as a form of implementing the Merdeka Belajar Kampus Merdeka (MBKM) education policy.